HAND-ASSISTED LAPAROSCOPIC DONOR NEPHRECTOMY. THE FIRST RUSSIAN EXPERIENCE - S. V. Gautier; O. E. Lutsevich; Y. G. Moysyuk; E. A. Gallyamov; D. N. Panchenkov; A. S. Efimkin; A. V. Baranov (Вестник трансплантологии и искусственных органов)
The first experience of hand-assisted laparoscopic donor nephrectomy is described in the article. A new technique of the operation and it’s results are discussed in details. Advantages of this type of the operation in comparison with open and full laparoscopic techniques are presented.